Mental health needs and service use in a national sample of adult cancer survivors in the USA: has psychosocial care improved?. Issue 1 (13th May 2014) - Whitney, Robin L.; Bell, Janice F.; Bold, Richard J.; Joseph, Jill G.
Abstract Objective This study aims to estimate and test temporal differences in mental health (MH) need and service use among adult cancer survivors nationally before and after important policy recommendations for psychosocial cancer care. Methods Adults (n = 58, 585) from the National Health Interview Survey, 2005 and 2010, were categorized as having (1) no chronic disease, (2) chronic disease other than cancer, (3) cancer without other chronic disease, and (4) cancer with other chronic disease. In these groups, we compared psychological distress, MH visits, and unmet need for MH services. Survey‐weighted logistic regression was used to model these variables as functions of disease status and sociodemographic covariates and the interactions of disease status and survey year. Results Whereas the proportion of individuals with psychological distress and MH visits was significantly higher in 2010 versus 2005 for the no chronic disease group, the only group with significantly lower unmet need in 2010 versus 2005 was the cancer with other chronic disease group (5.3% vs. 3.0%, p < 0.05). In adjusted models, cancer survivors with other chronic disease had significantly lower odds of unmet need in 2010 (odds ratio 1.38; 95% confidence interval 0.85, 2.25) than in 2005 (odds ratio 3.32; 95% confidence interval 2.28, 4.83). Conclusions We find evidence of MH care quality improvement among cancer survivors between 2005 and 2010, a period that coincides with policy and clinical attention to psychosocial cancer care. These efforts may have reduced, but not eliminated, unmet need for MH services among cancer survivors. Copyright © 2014 John Wiley & Sons, Ltd.